**Solve the following simultaneous equations. 2x – 3y = 5 , x – 2y = 4 **

We have to solve the following set of simultaneous equations:

2x - 3y = 5 ...(1)

x - 2y = 4 ...(2)

From (2)

x - 2y = 4

=> x= 4 + 2y

Substitute in (1)

2( 4 + 2y) - 3y = 5

=> 8 + 4y - 3y = 5

=> y = -3

x = 4 + 2y

=> x = 4 + 2*(-3)

=> x = 4 - 6

=> x = -2

**We get x = -2 and y = -3**

**Solve the following simultaneous equations. x + 3y = 2 , 2x + 8y = 6 **

We have to solve the following set of simultaneous equations:

x + 3y = 2 ...(1)

2x + 8y = 6 ...(2)

2*(1) - (2)

=> 2x + 6y - 2x - 8y = 4 - 6

=> -2y = -2

=> y = -2/-2

=> y = 1

substitute in (1)

x + 3 = 2

=> x = 2 - 3

=> x = -1

**We get x = -1 and y = 1**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.